Patient Preferred Fixed Treatment Modalities For One Or Two Missing Teeth - An Institution Based Retrospective Study - CHANDRAPOOJA; ARIGA, PADMA; JEEVANANDAN, GANESH (The journal of contemporary issues in business and government, 2020)
Replacement of missing teeth represents the largest category among patients in clinics who are looking for better esthetic and/or functional teeth. The fixed partial denture (FPD) is one of the most commonly preferred definitive treatment options for a single missing tooth.To assess the patient preference of type of fixed treatment modalities a retrospective study was carried out using case records of 1208 patients who reported to the Department of Prosthodontics from June 2019 to March 2020.The number of patients preferring fixed treatment modalities for one or two missing teeth were observed from the case records and tabulated on a spreadsheet. The collected data was analysed by computer software SPSS version 21 using Chi square test indicating the level of significance.Fixed partial denture was taken as a treatment of choice in 52.2% of the patient and implant was taken as treatment of choice in 47.8% of the patients. Both fixed partial denture and implant treatment were opted more among the male patients than female patients. Below the age of 30 years fixed partial denture was opted by 197(16.31%) of patients and implant by 163(13.49%) patients. Between the age of 31-60 years 369 patients(32.78%) opted fixed partial denture and 380 patients(31.46%) opted implants as treatment of choice. Above the age of 60 years, 37 patients(3.06%) and 35 patients(2.90%) had fixed partial denture and implant respectively with 31- 60 years age group patients receiving maximum fixed treatments. Patient preferred treatment options with fixed prosthesis had no significant association with neither age(p value-0.50) nor gender(p value-0.20).